Evidence-based guidelines for the management of large hemispheric infarction : a statement for health care professionals from the Neurocritical Care Society and the German Society for Neuro-intensive Care and Emergency Medicine - Torbey, Michel T.; Boesel, Julian; Rhoney, Denise H.; Rincon, Fred; Staykov, Dimitre; Amar, Arun P.; Varelas, Panayiotis N.; Juettler, Eric; Olson, Daiwai; Huttner, Hagen; Zweckberger, Klaus; Sheth, Kevin N.; et al. (Neurocritical Care, 2015)
Large hemispheric infarction (LHI), also known as malignant middle cerebral infarction, is a devastating disease associated with significant disability and mortality. Clinicians and family members are often faced with a paucity of high quality clinical data as they attempt to determine the most appropriate course of treatment for patients with LHI, and current stroke guidelines do not provide a detailed approach regarding the day-to-day management of these complicated patients. To address this need, the Neurocritical Care Society organized an international multidisciplinary consensus conference on the critical care management of LHI. Experts from neurocritical care, neurosurgery, neurology, interventional neuroradiology, and neuroanesthesiology from Europe and North America were recruited based on their publications and expertise. The panel devised a series of clinical questions related to LHI, and assessed the quality of data related to these questions using the Grading of Recommendation Assessment, Development and Evaluation guideline system. They then developed recommendations (denoted as strong or weak) based on the quality of the evidence, as well as the balance of benefits and harms of the studied interventions, the values and preferences of patients, and resource considerations.
EVALuna2:22397